The Effect of Explosive Power Training on the Long Jump Ability of College Students - Ikadarny, Ikadarny; Syafruddin, Muhammad Akbar (Universitas Majalengka, 2024)
Long jump ability is influenced by various factors, one of which is physical condition. So that training is needed that can encourage the improvement of physical conditions such as training to increase the explosive power of leg muscles. This research is included in the experimental research category. Experimental research aims to investigate and improve the manifestation of explosive power in muscles. The sample in this study amounted to 17 people selected by total sampling technique. The stages in this study include taking pre-test data, providing treatment in the form of explosive power training, and taking post-test data. The data analysis technique used to answer the hypothesis is to use the paired sample T test. Based on the results of data analysis, the Sig. value of 0.000 <0.05 was obtained with a mean value for the pre-test of long jump ability of 3.2 and a mean value for the post-test of long jump of 4.3. So it can be concluded that leg muscle explosive power training has an effect in improving the long jump ability of PJKR-SD FIK UNM students with an increase of 34.4%.